1988
DOI: 10.2527/jas1988.6661371x
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Responses of Carcass and Reproductive Traits to Selection for Rate of Lean Growth in Swine

Abstract: Mass selection for an index of increased postweaning average daily gain and decreased backfat thickness was practiced for five generations. Litter size and weight for 221 gilt litters, birth weight and nipple number for 2,242 piglets and weaning weight at 42 d of age for 2,111 pigs were recorded. Carcass measurements were taken on 331 pigs. Differences between means of the lines (select control) were regressed on cumulative selection differential of the index. These regression coefficients were negative (P > .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
3
20
1
Order By: Relevance
“…Correlated responses reported here (Fig. 3, Table 2) agree with those of Cleveland et al (1988), who reported that index selection for ADG and backfat thickness for lean growth resulted in negative but non-significant correlated responses for TNB, NBA, and N42. Vangen (1980) reported positive correlated responses for TNB and NBA, but negative correlated responses for N42 to index selection for lean growth in a Norwegian Landrace line.…”
Section: Litter Size Traitssupporting
confidence: 80%
See 1 more Smart Citation
“…Correlated responses reported here (Fig. 3, Table 2) agree with those of Cleveland et al (1988), who reported that index selection for ADG and backfat thickness for lean growth resulted in negative but non-significant correlated responses for TNB, NBA, and N42. Vangen (1980) reported positive correlated responses for TNB and NBA, but negative correlated responses for N42 to index selection for lean growth in a Norwegian Landrace line.…”
Section: Litter Size Traitssupporting
confidence: 80%
“…This problem could be overcome by creating a synthetic line that contains a highly prolific native Chinese breed such as the Meishan (Bolet et al 1986;Bazer et al 1988;Bidanel et al 1989), along with American and European breeds, and then selecting the resulting line for LGR (Bidanel et al 1991;Webb 1998). Moreover, several studies (Vangen 1980;Cleveland et al 1988;Kerr and Cameron 1996) have demonstrated that selection for LGR in purebred lines does not result in significant negative correlated responses in litter traits.…”
mentioning
confidence: 99%
“…Generally, responses were small and not significantly different from zero (Fredeen and Mikami, 1986;Cleveland et al, 1988;Kerr and Cameron, 1995). However, Kerr and Cameron (1995) found that selection for certain aspects of lean growth rate that reduced daily feed intake, such as direct selection for reduced feed intake and selection for high lean food conversion ratio, caused a correlated reduction in litter size at birth.…”
Section: Discussionmentioning
confidence: 99%
“…(1977), and correlated responses in litter size from lean growth selection (Cleveland et al, 1988) or selection for components of growth that did not decrease feed intake (Kerr and Cameron, 1995) were not significant.…”
Section: Introductionmentioning
confidence: 99%
“…Bereskin (1984), Ferguson et al (1985), Cleveland et al (1988) and Kerr and Cameron (1996) reported negative genetic correlations of fattening and slaughter traits with reproductive traits. The correlations between weight gain and number of piglets per litter on day 21 were estimated by Bereskin (1984) to be r = -0.60.…”
Section: Discussionmentioning
confidence: 99%